A coated modified phosphate positive electrode composite material and preparation method thereof

Through the preparation method of coated modified phosphate positive electrode composite, the problems of low conductivity and insufficient ion diffusion speed of phosphate positive electrode materials are solved, and the conductivity and stability of the material are improved, which has great application value.

CN119176538BActive Publication Date: 2025-03-07SICHUAN FULIN NEW ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411695830.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-07
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing phosphate cathode materials have problems with low conductivity and insufficient ion diffusion speed in applications, which limit their performance improvement and application range.

Method used

The core of the phosphate positive electrode material is obtained by mixing the lithium source, doped metal source, phosphorus source and the first carbon source, and secondary sintering is performed with a nitrogen-rich precursor, a carbon quantum dot, and a second carbon source to form a coated modified phosphate positive electrode composite material, optimizing the charge transfer efficiency of the material surface.

Benefits of technology

It improves the conductivity, stability and reliability of the material, improves capacity and energy density, and has great application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176538B_ABST
    Figure CN119176538B_ABST
Patent Text Reader

Abstract

A coated modified phosphate positive electrode composite material and a preparation method thereof, relating to the field of material technology, wherein the preparation method comprises mixing a lithium source, a doped metal source, a phosphorus source and a first carbon source and then sintering to obtain a phosphate positive electrode material core; then mixing with a nitrogen- and carbon-rich precursor, carbon quantum dots and a second carbon source for secondary sintering to obtain a coated modified phosphate positive electrode composite material. The preparation method is simple to operate and has low requirements on equipment. It utilizes the surface localized π conjugated modification formed during thermal polymerization and the anchoring effect of carbon quantum dots to optimize the charge transfer efficiency on the material surface, improve the material capacity and energy density, and improve the material stability and reliability, and has great application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material technology, and in particular to a coated modified phosphate positive electrode composite material and a preparation method thereof. Background Art

[0002] In the field of lithium-ion batteries, phosphate materials have become ideal cathode materials due to their excellent thermal stability, safety and cycle life. Among them, phosphate materials such as lithium iron phosphate (LiFePO4) and lithium manganese phosphate (LiMnPO4) have been widely used in commercial batteries. However, these materials often face problems such as low conductivity and insufficient ion diffusion rate in practical applications, which limits their further performance improvement and application scope.

[0003] In order to improve the electrochemical performance of phosphate cathode materials, researchers have adopted a variety of strategies. For example, nano-processing is used to increase the specific surface area of ​​the material and improve the transmission rate of ions and electrons; doping or coating is used to improve the conductivity and structural stability of the material. However, traditional modification methods often have some shortcomings, such as limited modification effect, complex processing or high cost.

[0004] In recent years, carbon nitride (such as graphitic carbon nitride, g-C3N4) has been considered an effective choice for modified phosphate cathode materials due to its excellent conductivity, chemical stability and high specific surface area. After carbon nitride is combined with carbon materials, it can significantly improve the conductivity and electrochemical performance of the composite material. However, existing carbon nitride materials often lack an effective charge transfer mechanism when combined with phosphate, which limits the further improvement of their performance. Summary of the invention

[0005] The object of the present invention is to provide a coated modified phosphate positive electrode composite material and a preparation method thereof, which optimizes the charge transfer efficiency of existing carbon nitride materials, thereby effectively improving the electrical conductivity, stability, reliability, etc. of the material.

[0006] The embodiment of the present invention is achieved as follows:

[0007] A method for preparing a coated modified phosphate positive electrode composite material, comprising:

[0008] The lithium source, the doped metal source, the phosphorus source and the first carbon source are mixed and sintered to obtain a phosphate positive electrode material core;

[0009] The phosphate cathode material core is mixed with a nitrogen- and carbon-rich precursor, carbon quantum dots, and a second carbon source and then subjected to secondary sintering to obtain a coated and modified phosphate cathode composite material;

[0010] The doping metal source includes at least one of an iron source and a manganese source; and the second carbon source is an organic carbon source having multiple hydroxyl groups in its molecular structure.

[0011] A coated modified phosphate positive electrode composite material is prepared by the preparation method of the coated modified phosphate positive electrode composite material.

[0012] The beneficial effects of the embodiments of the present invention are:

[0013] The embodiment of the present invention provides a coated modified phosphate positive electrode composite material and a preparation method thereof, wherein the preparation method comprises mixing a lithium source, a doped metal source, a phosphorus source and a first carbon source and then sintering to obtain a phosphate positive electrode material core; and then mixing with a nitrogen- and carbon-rich precursor, carbon quantum dots and a second carbon source for secondary sintering to obtain a coated modified phosphate positive electrode composite material. The preparation method is simple to operate, has low requirements on equipment, and utilizes the surface localized π conjugated modification formed during thermal polymerization and the anchoring effect of carbon quantum dots to optimize the charge transfer efficiency on the material surface, improve the capacity and energy density of the material, and improve the stability and reliability of the material, and has great application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0015] Figure 1 It is a schematic diagram of the principle of forming an in-plane π-conjugated structure according to the present invention;

[0016] Figure 2 This is the SEM spectrum of the coated and modified phosphate positive electrode composite material provided in Example 1 of the present invention;

[0017] Figure 3 This is a test chart of 0.1C charge and discharge capacity of button cells prepared from the positive electrode materials of Example 1 and Comparative Examples 1 to 4 of the present invention; DETAILED DESCRIPTION

[0018] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0019] The following is a detailed description of a coated modified phosphate positive electrode composite material according to an embodiment of the present invention, and a preparation method and application thereof.

[0020] A method for preparing a coated modified phosphate positive electrode composite material, comprising:

[0021] S1. The lithium source, the doped metal source, the phosphorus source and the first carbon source are mixed and sintered to obtain a phosphate cathode material core;

[0022] S2. The phosphate cathode material core is mixed with a nitrogen- and carbon-rich precursor, carbon quantum dots, and a second carbon source and then sintered to obtain a coated modified phosphate cathode composite material;

[0023] The doping metal source includes at least one of an iron source and a manganese source; and the second carbon source is an organic carbon source having multiple hydroxyl groups in its molecular structure.

[0024] In recent years, carbon nitride (such as graphitic carbon nitride, g-C3N4) has been considered an effective choice for modified phosphate cathode materials due to its excellent conductivity, chemical stability and high specific surface area. After carbon nitride is combined with carbon materials, it can significantly improve the conductivity and electrochemical performance of the composite material. However, existing carbon nitride materials often lack an effective charge transfer mechanism when combined with phosphate, which limits the further improvement of their performance.

[0025] After extensive research, the inventors found that the introduction of graphite carbon rings with similar aromatic structures into carbon nitride can form a local π-conjugated electric field with the triazine unit in carbon nitride. This in-plane π-conjugated electrical modification can generate a gradient charge potential level during the interfacial charge transport process, thereby driving charge transfer and improving the conductivity of the material. At the same time, the carbonaceous network porous structure formed by the coupling of graphite carbon rings and carbon nitride can ensure the rapid diffusion of lithium ions and maintain the structural stability of the material. This in-plane π-conjugated structure can be achieved by the following methods: Figure 1 As shown in the figure, the nitrogen- and carbon-rich precursors are first subjected to thermal polymerization at a relatively low temperature to form melem structural units; the hydroxyl groups of the organic carbon source are then used to perform nucleophilic substitution and dehydration on the amino groups of the melem structure to form new sp2 hybridization, thereby forming structural units in which the cyclized in-plane triazine structure and the graphite carbon ring coexist; finally, as the temperature increases, these triazine carbon ring motifs are further polymerized through π-conjugated bonds to form the final planar C ring / g-C3N4 structure, the plane C ring / g-C3N4 contains an in-plane π-conjugated structure composed of a triazine structure and a graphite carbon ring.

[0026] Among them, the lithium source, doped metal source, phosphorus source, first carbon source, second carbon source, nitrogen- and carbon-rich precursors, and carbon quantum dots are all commercially available materials and can be directly obtained and used through commercial channels.

[0027] Optionally, the second carbon source includes at least one of glucose, sucrose, cyclohexane hexol and lactose; the amount of the second carbon source added is 0.1wt%~1.0wt% of the phosphate positive electrode composite material. The above carbon sources all contain a polyhydroxyl carbon ring structure, which can form a new sp2 hybridization through nucleophilic substitution and dehydration.

[0028] The nitrogen- and carbon-rich precursor includes at least one of melamine, dicyandiamide, cyanamide, urea and thiourea; the nitrogen- and carbon-rich precursor is converted during the sintering process and forms the required triazine structure motif. The amount of the nitrogen- and carbon-rich precursor added is 0.1wt% to 1.0wt% of the phosphate positive electrode composite material. Under the above ratio, the conversion efficiency of the nitrogen- and carbon-rich precursor is high, and the performance of the product is better.

[0029] Furthermore, the mass ratio of the nitrogen-rich and carbon-rich precursor, the carbon quantum dots, and the second carbon source is 1: (0.1-0.5): (0.1-1). Within this ratio range, C ring The proportion of triazine structure and graphite carbon ring in / g-C3N4 is more reasonable, and the coordination effect with carbon quantum dots is better, which can provide better electron conduction efficiency.

[0030] The doping metal includes at least one of ferrous oxalate, ferric phosphate, ferric acetate, ferric nitrate, ferrous oxide, manganese oxalate, manganese tetraoxide, manganese sulfate, manganese acetate and manganese nitrate; the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate and lithium acetate; the phosphorus source includes at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, lithium dihydrogen phosphate and phosphoric acid.

[0031] Preferably, the molar ratio of Li:P:(Fe and / or Mn) provided by the lithium source, the doped metal source, and the phosphorus source is (0.99-1.05):(0.98-1.01):(0.98-1.01). The overall performance of the material is better within the above ratio range.

[0032] The first carbon source includes at least one of carbon black, acetylene black, ammonium bicarbonate, glucose, sucrose, cyclohexane hexol, lactose, polyethylene glycol and citric acid. The present invention does not have too strict restrictions on the type of the first carbon source, which can be an inorganic carbon source or an organic carbon source. The addition amount of the first carbon source is 0.1wt%~0.5wt% of the phosphate positive electrode composite material.

[0033] Furthermore, the lithium source, the doped metal source, the phosphorus source and the first carbon source are mixed and ground to a particle size of 0.2-0.8 μm before sintering. The material after grinding can have a larger contact area, thereby achieving a better reaction effect. Grinding can be performed by wet grinding, and after grinding, spray drying or freeze drying is performed to obtain a powdered sintering material. The sintering temperature is 500-800°C and the time is 5-12 hours. At the above temperature, it is conducive to the rapid molding of the material.

[0034] Optionally, the secondary sintering is to first heat up to 200-400°C at a rate of 1-5°C / min, keep warm for 1-3 hours, then heat up to 500-700°C, and keep warm for 2-6 hours. The reaction at 200-400°C can effectively control the reaction process, allowing the nitrogen-rich and carbon-rich precursors to fully react and increase the conversion rate of forming the melem structure. Then gradually increase the temperature so that the hydroxyl groups of the organic carbon source can better undergo nucleophilic reactions and dehydrate to form the final product.

[0035] The embodiment of the present invention also provides a coated modified phosphate positive electrode composite material, which is prepared by the above-mentioned method for preparing the coated modified phosphate positive electrode composite material. The coating layer of the material has an in-plane π conjugated structure and carbon quantum dots, and by optimizing the charge transfer efficiency, a higher capacity and energy density are obtained, and better stability and reliability are obtained.

[0036] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0037] Example 1

[0038] This embodiment provides a coated modified phosphate positive electrode composite material, and the preparation method thereof is as follows:

[0039] S1. Lithium carbonate, ferrous oxalate, manganese tetraoxide, lithium dihydrogen phosphate and glucose (Li:P:Mn:Fe=1.04:1:0.582:0.388) were mixed and dispersed in a proper amount of water to form a uniform mixed slurry A; wherein the added amount of glucose was 0.2wt%.

[0040] The mixed slurry A is ultra-finely ground until the average particle size is reduced to 0.2-0.8 μm, and then spray-dried to obtain a powdered sintering material.

[0041] S2. The sintered material of step S1 is sintered in a nitrogen atmosphere, and the sintering temperature is set to 500° C. and kept for 6 h to obtain the core of the phosphate positive electrode material.

[0042] S3. Mix melamine, carbon quantum dots, glucose and the above-mentioned lithium iron phosphate positive electrode material matrix according to a stoichiometric ratio and evenly disperse them in water to obtain a mixed slurry B; wherein the amount of melamine used is 0.7wt%, the amount of carbon quantum dots added is 0.2wt%, and the amount of glucose added is 0.3wt%.

[0043] The mixed slurry B is ultra-finely ground to reduce the average particle size to 0.2-0.5 μm, and then spray-dried to obtain a sintered material.

[0044] S4. The sintered material of step S3 was subjected to two stages of heat preservation at 300° C. for 1 h and heating at 600° C. for 4 h in a nitrogen atmosphere, and finally a coated modified lithium manganese iron phosphate positive electrode composite material was obtained.

[0045] Figure 2 The SEM spectrum of the coated and modified lithium manganese iron phosphate positive electrode composite material is displayed. The coated and modified lithium manganese iron phosphate positive electrode composite material has good sphericity in micromorphology, relatively uniform particle size distribution, and better compaction density.

[0046] Example 2

[0047] This embodiment provides a coated modified phosphate positive electrode composite material, and the preparation method thereof is as follows:

[0048] S1. Lithium carbonate, manganese tetraoxide, ammonium dihydrogen phosphate and glucose (Li:P:Mn=1.04:1:0.97) were mixed and dispersed in a suitable amount of water to form a uniform mixed slurry A; wherein the added amount of glucose was 0.4wt%.

[0049] The mixed slurry A is ultra-finely ground until the average particle size is reduced to 0.2-0.8 μm, and then spray-dried to obtain a powdered sintering material.

[0050] S2. The sintered material of step S1 is sintered in a nitrogen atmosphere at a sintering temperature of 500° C. for 6 hours to obtain a core of a phosphate positive electrode material.

[0051] S3. Urea, carbon quantum dots, glucose and the above-mentioned lithium iron phosphate positive electrode material matrix are mixed in a stoichiometric ratio and evenly dispersed in water to obtain a mixed slurry B; wherein the amount of urea used is 0.7wt%, the amount of carbon quantum dots added is 0.2wt%, and the amount of glucose added is 0.3wt%.

[0052] The mixed slurry B is ultra-finely ground to reduce the average particle size to 0.2-0.5 μm, and then spray-dried to obtain a sintered material.

[0053] S4. The sintered material of step S3 was subjected to two stages of heat preservation at 300° C. for 1 h and heating at 600° C. for 4 h in a nitrogen atmosphere, to finally obtain a coated modified lithium manganese phosphate positive electrode composite material.

[0054] Example 3

[0055] This embodiment provides a coated modified phosphate positive electrode composite material, and the preparation method thereof is as follows:

[0056] S1. Lithium carbonate, ferrous oxalate, ammonium dihydrogen phosphate and glucose (Li:P:Fe=1.04:1:0.97) were mixed and dispersed in an appropriate amount of water to form a uniform mixed slurry A; wherein the added amount of glucose was 0.1wt%.

[0057] The mixed slurry A is ultra-finely ground until the average particle size is reduced to 0.2-0.8 μm, and then spray-dried to obtain a powdered sintering material.

[0058] S2. The sintered material of step S1 is sintered in a nitrogen atmosphere at a sintering temperature of 550° C. for 6 h to obtain a core of a phosphate positive electrode material.

[0059] S3. Mix melamine, carbon quantum dots, glucose and the above-mentioned lithium iron phosphate positive electrode material matrix according to a stoichiometric ratio and evenly disperse them in water to obtain a mixed slurry B; wherein the amount of melamine used is 0.7wt%, the amount of carbon quantum dots added is 0.2wt%, and the amount of glucose added is 0.3wt%.

[0060] The mixed slurry B is ultra-finely ground to reduce the average particle size to 0.2-0.5 μm, and then spray-dried to obtain a sintered material.

[0061] S4. The sintered material of step S3 was subjected to two stages of heat preservation at 300° C. for 1 h and heating at 600° C. for 4 h in a nitrogen atmosphere, and finally a coated modified lithium iron phosphate positive electrode composite material was obtained.

[0062] Example 4

[0063] This embodiment provides a coated modified phosphate positive electrode composite material, and the preparation method thereof is as follows:

[0064] S1. Lithium hydroxide, iron phosphate, manganese tetraoxide, phosphoric acid and acetylene black (Li:P:Mn:Fe=1.04:1:0.582:0.388) are mixed and dispersed in a proper amount of water to form a uniform mixed slurry A; wherein the addition amount of acetylene black is 0.3wt%.

[0065] The mixed slurry A is ultra-finely ground until the average particle size is reduced to 0.2-0.8 μm, and then spray-dried to obtain a powdered sintering material.

[0066] S2. The sintered material of step S1 is sintered in a nitrogen atmosphere at a temperature of 650°C for 5 h to obtain a core of the phosphate positive electrode material.

[0067] S3. Dicyandiamide, carbon quantum dots, cyclohexanehexol and the above-mentioned lithium iron phosphate positive electrode material matrix are mixed in a stoichiometric ratio and evenly dispersed in water to obtain a mixed slurry B; wherein the amount of dicyandiamide used is 0.6wt%, the amount of carbon quantum dots added is 0.2wt%, and the amount of cyclohexanehexol added is 0.4wt%.

[0068] The mixed slurry B is ultra-finely ground to reduce the average particle size to 0.2-0.5 μm, and then spray-dried to obtain a sintered material.

[0069] S4. The sintered material of step S3 was subjected to two stages of heat preservation at 200° C. for 3 h and heating at 600° C. for 5 h in a nitrogen atmosphere, and finally a coated modified lithium manganese iron phosphate positive electrode composite material was obtained.

[0070] Example 5

[0071] This embodiment provides a coated modified phosphate positive electrode composite material, and the preparation method thereof is as follows:

[0072] S1. Lithium acetate, manganese carbonate, ferrous oxalate, diammonium hydrogen phosphate and citric acid (Li:P:Mn:Fe=1.03:1:0.582:0.388) were mixed and dispersed in an appropriate amount of water to form a uniform mixed slurry A; wherein the added amount of citric acid was 0.3wt%.

[0073] The mixed slurry A is ultra-finely ground until the average particle size is reduced to 0.2-0.8 μm, and then spray-dried to obtain a powdered sintering material.

[0074] S2. The sintered material of step S1 is sintered in a nitrogen atmosphere at a sintering temperature of 500° C. for 10 h to obtain a core of a phosphate positive electrode material.

[0075] S3. Mix melamine, carbon quantum dots, lactose and the above-mentioned lithium iron phosphate positive electrode material matrix according to a stoichiometric ratio and evenly disperse them in water to obtain a mixed slurry B; wherein the amount of melamine used is 0.5wt%, the amount of carbon quantum dots added is 0.2wt%, and the amount of lactose added is 0.5wt%.

[0076] The mixed slurry B is ultra-finely ground to reduce the average particle size to 0.2-0.5 μm, and then spray-dried to obtain a sintered material.

[0077] S4. The sintered material of step S3 was subjected to two stages of heat preservation at 400° C. for 1 h and heating at 500° C. for 6 h in a nitrogen atmosphere, to finally obtain a coated modified lithium manganese iron phosphate positive electrode composite material.

[0078] Comparative Example 1

[0079] This comparative example provides a coated modified phosphate positive electrode composite material, and its preparation method is basically the same as that of Example 1, except that in step S3, no carbon quantum dots are added.

[0080] Comparative Example 2

[0081] This comparative example provides a coated modified phosphate positive electrode composite material, and its preparation method is basically the same as that of Example 1, except that in step S3, glucose is not added.

[0082] Comparative Example 3

[0083] This comparative example provides a coated modified phosphate positive electrode composite material, and its preparation method is basically the same as that of Example 1, except that in step S3, melamine is not added.

[0084] Comparative Example 4

[0085] This comparative example provides a coated modified phosphate positive electrode composite material, and its preparation method is basically the same as that of Example 1, except that in step S3, carbon quantum dots and glucose are not added.

[0086] Test Example 1

[0087] The coated modified phosphate positive electrode composite materials provided in Example 1 and Comparative Examples 1 to 4 were used as battery positive electrode materials for assembly and testing. The gram capacity at a rate of 0.1C was tested respectively. The charge and discharge curves are shown in FIG. Figure 3 The test results are shown in Table 1.

[0088] Table 1. Test results of coated modified phosphate cathode composite materials

[0089]

[0090] It can be clearly seen from the data analysis of Table 1 that after precisely controlling the type of raw materials and the amount of the second carbon source added, the products obtained in Examples 1 to 5 of the present invention exhibit excellent performance characteristics, especially in terms of charge and discharge performance. Specifically, through its unique preparation process, Examples 1 to 5 successfully achieved a high compaction density of 2.325 to 2.562 g / cm³, an indicator that is in a leading position among similar products. At the same time, the resistivity of the powder under this process is only 6.247 to 11.966 Ω·cm, and this excellent resistivity ensures efficient transmission of electrons in the material. In addition, at a rate of 0.1C, the first discharge capacity of Examples 1 to 5 is as high as 152.852 mAh / g or more, which fully demonstrates its great potential in practical applications.

[0091] In order to comprehensively evaluate the performance of the product, we conducted comparative experiments without composite modification (Comparative Examples 1~4). Specifically, in Comparative Example 1, carbon quantum dots were not used, and the powder resistivity of the product was significantly improved to 30.547 Ω·cm, while the first discharge capacity was significantly reduced to 150.061mAh / g. In Comparative Examples 2 and 3, the second carbon source and the nitrogen- and carbon-rich precursors were not added, respectively, and the coating layer could not form a π-conjugated structure, which also led to an increase in resistivity and a decrease in the first discharge capacity. In Comparative Example 4, no carbon quantum dots and a second carbon source were added at the same time, which had the most significant effect on the material, with a powder resistivity of up to 83.127 Ω·cm and a first discharge capacity of 146.194mAh / g. The above results show that under these comparative conditions, the performance of the product has decreased significantly, specifically manifested in an increase in powder resistivity and a significant decrease in first discharge capacity. These comparative data strongly demonstrate the important role of surface localized π-conjugated modification and carbon quantum anchoring in improving product performance.

[0092] In summary, the embodiment of the present invention provides a coated modified phosphate positive electrode composite material and a preparation method thereof, wherein the preparation method comprises mixing a lithium source, a doped metal source, a phosphorus source and a first carbon source and then sintering to obtain a phosphate positive electrode material core; and then mixing with a nitrogen- and carbon-rich precursor, carbon quantum dots and a second carbon source for secondary sintering to obtain a coated modified phosphate positive electrode composite material. The preparation method is simple to operate, has low requirements on equipment, and utilizes the surface localized π conjugated modification formed during thermal polymerization and the anchoring effect of carbon quantum dots to optimize the charge transfer efficiency on the material surface, improve the capacity and energy density of the material, and improve the stability and reliability of the material, and has great application value.

[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a coated modified phosphate positive electrode composite material, characterized in that: include: The lithium source, the doped metal source, the phosphorus source and the first carbon source are mixed and sintered to obtain a phosphate positive electrode material core; The phosphate positive electrode material core is mixed with a nitrogen- and carbon-rich precursor, carbon quantum dots, and a second carbon source and then subjected to secondary sintering to obtain a coated and modified phosphate positive electrode composite material; Wherein, the doping metal source includes at least one of an iron source and a manganese source; the second carbon source is an organic carbon source having multiple hydroxyl groups in its molecular structure; The second carbon source includes at least one of glucose, sucrose, cyclohexane hexol and lactose; the added amount of the second carbon source is 0.1wt% to 1.0wt% of the phosphate positive electrode composite material; The nitrogen- and carbon-rich precursor includes at least one of melamine, dicyandiamide, cyanamide, urea and thiourea; and the added amount of the nitrogen- and carbon-rich precursor is 0.1 wt% to 1.0 wt% of the phosphate positive electrode composite material.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the nitrogen- and carbon-rich precursor, the carbon quantum dots and the second carbon source is 1:0.1~0.5:0.1~1.

3. The preparation method according to claim 1, wherein the doping metal comprises at least one of ferrous oxalate, ferric phosphate, ferric acetate, ferric nitrate, ferrous oxide, manganese oxalate, manganese tetraoxide, manganese carbonate, manganese sulfate, manganese acetate and manganese nitrate; the lithium source comprises at least one of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate and lithium acetate; and the phosphorus source comprises at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, lithium dihydrogen phosphate and phosphoric acid.

4. The preparation method according to claim 1, characterized in that: The first carbon source includes at least one of carbon black, acetylene black, ammonium bicarbonate, glucose, sucrose, cyclohexanehexol, lactose, polyethylene glycol and citric acid; the added amount of the first carbon source is 0.1wt%~0.5wt% of the phosphate positive electrode composite material.

5. The preparation method according to claim 1, characterized in that: The lithium source, the doping metal source, the phosphorus source and the first carbon source are mixed, ground to a particle size of 0.2-0.8 μm, and then sintered.

6. The preparation method according to claim 5, characterized in that: The sintering temperature is 500~800℃ and the time is 5~12h.

7. The preparation method according to claim 1, characterized in that: The secondary sintering is to first increase the temperature to 200~400℃ at a rate of 1~5℃ / min, keep it warm for 1~3h, then increase the temperature to 500~700℃, and continue to keep it warm for 2~6h.

Citation Information

Patent Citations

  • Preparation method of high-performance lithium iron phosphate positive electrode material

    CN116062725A